Millennial Attributes and Educational Management in the Schools Division of Roxas City - Jan Kennith Dorde Agapito; Rev. Fr. Michael B. Vasquez (President University, 2023)
The rise of millennials, and its various distinguishing characteristics are causing substantial changes in the workplace. A few of the traits typically associated with this generation include flexibility, self-confidence, and technological competence. This cohort further entails management and leadership styles akin to them. Through a descriptive correlational approach, this study explores the extent of the millennial attributes in terms of values and behaviors and to determine whether there is a correlation on the degree of educational management in terms of leadership and management styles in the Schools Division of Roxas City for school year 2022-2023 as perceived by the 247 out of 317 public elementary school teachers. The purpose of this study is to provide data on the academe on how elementary teachers perceived their school heads in dealing with the educational system in their respective schools whether they possess the millennial characteristics, skills, and competence that is needed in today’s workplace, practically and timely. The sample size was taken from the total population with a margin of error set at 0.03 using the Slovin’s formula. A researcher-made questionnaire, frequency count, percentage, mean, t-test, and Pearson r correlation coefficient were used in the collection and analysis of data. The findings showed that the extent of millennial attributes and the degree of educational management was found to be very highly evident. The extent of millennial attributes and degree of educational management have an insignificant effect on teachers’ perception based on their socio-demographic profile. Finally, the extent of millennial attributes and educational management were significantly interconnected. It is imperative therefore that schools may consider the millennial attributes of human resource in the workplace. Future researchers are recommended to further the constructs of millennial attributes and educational management in the school.